Traversing the path to success in bariatric surgery: the fundamental role of bariatric endoscopy - Dorelo, Rodrigo (2024)
Obesity has become a growing global epidemic, demanding effective solutions for its management. Bariatric-metabolic surgery is currently the best therapeutic option for patients with morbid obesity and associated comorbidities. This review article addresses the importance of endoscopy in the preoperative and postoperative evaluation, as well as in the detection and management of complications associated with bariatric surgery.